Binmas Unit Counseling Model in Maintaining Harkamtibmas in Semanding Police - Carlos, Juan (Police Studies Review, 2024)
Security and order are the responsibilities of the Indonesian National Police as protectors, servants, and guardians of society. Community policing serves as the first step in Polri's preemptive approach to the community through outreach. The outreach conducted by the Police Community Development Officer in maintaining security and order in society is one of the preemptive methods employed by Polri to prevent crime as early as possible by providing guidance and outreach to all segments of society. Outreach is carried out through various methods including discussions, lectures, counseling, community safety entertainment stages, and community policing messages through print or social media, thus the researcher focuses on the community policing officer’s outreach model. The researcher utilizes theories and concepts in this final project. The theories used are the Shannon-Weaver theory and the community policing theory, while the concepts used include the model concept, outreach concept, community policing concept, and community safety concept. The research results show that: 1) The outreach conducted by community policing of Semanding Resort is in line with the main tasks of Community policing (Article 27 of Police Regulation No. 3 of 2015), which are community development, early detection, and mediation/negotiation to create a conducive environment in villages/urban areas. 2) The communication model used for outreach and guidance in the Semanding area, based on research results, is the discussion model. 3) The community fully supports the implementation of Community policing outreach by collaborating in maintaining security and order in the Semanding area. 4) Factors affecting community policing officer’s outreach in Semanding Resort are time, budget, personnel resources, and community resources. 5) The effectiveness of the method is seen through its quality, and the method with relatively good effectiveness and suitability in the Semanding area is the discussion method.